Improving reporting of meta‐ethnography: The eMERGe reporting guidance. Issue 3 (15th January 2019) - France, Emma F.; Cunningham, Maggie; Ring, Nicola; Uny, Isabelle; Duncan, Edward A.S.; Jepson, Ruth G.; Maxwell, Margaret; Roberts, Rachel J.; Turley, Ruth L.; Booth, Andrew; Britten, Nicky; Flemming, Kate; et al.
Abstract: Aims: The aim of this study was to provide guidance to improve the completeness and clarity of meta‐ethnography reporting. Background: Evidence‐based policy and practice require robust evidence syntheses which can further understanding of people's experiences and associated social processes. Meta‐ethnography is a rigorous seven‐phase qualitative evidence synthesis methodology, developed by Noblit and Hare. Meta‐ethnography is used widely in health research, but reporting is often poor quality and this discourages trust in and use of its findings. Meta‐ethnography reporting guidance is needed to improve reporting quality. Design: The eMERGe study used a rigorous mixed‐methods design and evidence‐based methods to develop the novel reporting guidance and explanatory notes. Methods: The study, conducted from 2015 to 2017, comprised of: (1) a methodological systematic review of guidance for meta‐ethnography conduct and reporting; (2) a review and audit of published meta‐ethnographies to identify good practice principles; (3) international, multidisciplinary consensus‐building processes to agree guidance content; (4) innovative development of the guidance and explanatory notes. Findings: Recommendations and good practice for all seven phases of meta‐ethnography conduct and reporting were newly identified leading to 19 reporting criteria and accompanying detailed guidance. Conclusion: The bespoke eMERGe Reporting Guidance, which incorporates new methodological developments and advances the methodology, can help researchers to report the important aspects of meta‐ethnography. Use of the guidance should raise reporting quality. Better reporting could make assessments of confidence in the findings more robust and increase use of meta‐ethnography outputs to improve practice, policy, and service user outcomes in health and other fields. This is the first tailored reporting guideline for meta‐ethnography. This article is being simultaneously published in the following journals: Journal of Advanced Nursing, Psycho‐oncology, Review of Education, and BMC Medical Research Methodology .